Consumer and Corporate Debt in a 3D Macroeconomic Model - Emilia G. Marsellou; Stylianos Kotsios (Mathematics)
We build on the literature of consumer debt–income inequality nexus, by developing a post-Keynesian model of growth and income distribution that incorporates both consumer and corporate borrowing. Specifically, we examine a non-linear dynamic system of three differential equations of workers’ debt-to-capital ratio, corporate debt-to-capital ratio, and the accumulation rate. We conduct simulations to solve the system for the long-run equilibrium points and examine local stability using the Routh–Hurwitz conditions. Additionally, we conduct a comparative statics analysis and investigate the stability of the model using a measure of the maximum distance among the three equilibrium points. Our key findings suggest that although our model shares several quantitative and qualitative aspects with the 2 × 2 models, the inclusion of corporate debt alters the impact of parameter changes on macroeconomic stability. This incorporation increases the number of parameters that have differing effects on stability across various scenarios. The ratio of external-to-internal borrowing, along with the interest rate, is among the few parameters that consistently undermines macroeconomic stability across all scenarios.